Nutrient-Dependent Impact of Microbes on Drosophila suzukii Development - Bing, XiaoLi (mBio, 2018)
Drosophila suzukii Matsumura is an invasive species of vinegar fly that has become a prominent pest of berries and other soft-skinned fruits. Unlike most other Drosophila species, female D. suzukii flies lay their eggs in ripening and ripe fruits and larvae develop within the fruit. To understand how D. suzukii larvae utilize ripe and ripening fruits, which usually have low levels of protein, we investigated the microbiota of field-captured and laboratory-reared D. suzukii flies and further examined the combined influence of diet and microbes on host fitness. Field-captured flies were associated with diverse microbiota, which varied significantly with sampling location and season. In contrast, laboratory-reared flies possessed strikingly lower bacterial abundance and diversity. A comparison of conventionally reared (CR) and germ-free (GF) flies revealed that the microbiota of D. suzukii does not alter its development significantly but decreases its life span under conditions of a nutrient-sufficient diet. However, the microbiota is essential for D. suzukii development on strawberry-based or blueberry-based fruit diets. This developmental failure could be rescued by reassociation with single bacterial or fungal species or by the addition of a high quantity of heat-killed microbes. In addition, we found that proteins are limiting with respect to fly development on fruit-based diets and that GF flies show signs of protein starvation. Taken together, our study results demonstrate that the microbiota provides key proteins required for the development of D. suzukii reared on fresh fruit. Our work shows that the impact of microbes on fly fitness depends strongly on nutritional conditions.